Design and Studying the Effect of Inner Bore Diameter of Unipolar Lens - Rafa Y. J. AL-Salih; Mohammed K. A. AL-Janan (Al-Mustansiriyah Journal of Science, 2022)
This work investigated the development of magnetic and optical properties and the invention of a previously unused lens. Many new designs have been suggested for a unipolar magnetic lens based on changing the width of the inner bore and fixing the other geometrical parameters of the lens to improve the performance of unipolar magnetic lenses. The investigation of a study of each design included the calculation of its axial magnetic field the magnetization of the lens in addition to the magnetic flux density using Finite Element Method (FEM). it was found that the best magnetizing properties, the highest value of magnetic flux and the lowest value of band width of the axial magnetic field strength have been obtained when the width of the inner cavity was (55 mm). The effect of current density on the optical properties has been also studied, and it was found that the optical properties have been improved also, and the chromatic and spherical aberration values have decreased significantly. Thus, the lens (55 mm) was chosen as the best design among the proposed designs.